2015
DOI: 10.1002/pc.23763
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of ultra-high molecular weight polyethylene fiber by different kinds of SiO2nanoparticles

Abstract: We successfully improved the interfacial adhesion strength between ultra‐high molecular weight polyethylene (UHMWPE) fiber and resin by the surface modification of UHMWPE fiber with two kinds of SiO2 nanoparticles through gel spinning process. Modified effect of treated SiO2 nanoparticles by coupling agent was superior to original SiO2 nanoparticles. Compared with unmodified fibers, pull‐out tests of modified UHMWPE/treated SiO2 fibers revealed that interfacial adhesion strength increased by the maximum of 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…According to curves (B) and (C), the OH content increased after the silica sol treatment, and the vibration peaks of SiOSi and SiO increased to different extents. By comparing with the conclusions of previous researchers, 34 it is shown that SiO 2 was adsorbed on the surface of ceramic microspheres. The SiOSi and SiO vibration peaks in curve (B) are larger than those in curve (C), indicating that the SiOSi bond was generated by SiO 2 and microspheres after heat treatment.…”
Section: Resultssupporting
confidence: 58%
“…According to curves (B) and (C), the OH content increased after the silica sol treatment, and the vibration peaks of SiOSi and SiO increased to different extents. By comparing with the conclusions of previous researchers, 34 it is shown that SiO 2 was adsorbed on the surface of ceramic microspheres. The SiOSi and SiO vibration peaks in curve (B) are larger than those in curve (C), indicating that the SiOSi bond was generated by SiO 2 and microspheres after heat treatment.…”
Section: Resultssupporting
confidence: 58%
“…Although the high molecular weight of UHMWPE endows many excellent properties, it also brings many difficulties in the processing of the material. 3,4 UHMWPE has an extremely high melt viscosity and very weak flowability (melt flow rate is near 0 g 10 min À1 ). 3,5 This is a direct consequence of the fact that UHMWPE cannot be processed on conventional extruders and injection molding machines.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in a number of applications in industry and civilian, such as bearings, wear‐resistant pipes, skis and artificial bone replacement materials. Although the high molecular weight of UHMWPE endows many excellent properties, it also brings many difficulties in the processing of the material 3,4 . UHMWPE has an extremely high melt viscosity and very weak flowability (melt flow rate is near 0 g 10 min −1 ) 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…An ultra-high molecular weight polyethylene (UHMWPE) fiber is characterized by high strength, low density, and outstanding toughness [ 1 , 2 , 3 ]. Nowadays, it has played a vital role in individual protection, armor protection, and other essential areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%